The Effectiveness of Mind Reading Game in Teaching Grammar - Nur Faradillah (Journal of Languages and Language Teaching, 2018)
This research was aimed to find out the effectiveness of Mind Reading Game in teaching grammar. This research was experimental design. The population of this study was the second grade students of MA Darul Kamilin which consisted of two classes. One classes were chosen as the samples, those were XI A Class as experimental group consisted of twenty three students and XI B Class as control group consisted twenty three students. They were chosen by using quasi experimental. Experimental group was treated by Mind Reading Game and control group was treated by Mind Game. The instrument that was used objective test in forms of multiple choices. Then, the scores were analyzed by using statistical analysis. It showed the mean score of experimental group was 20,34 while the mean score control group was 16,34 and the value of t (t test) = -4,756 was higher than  (t table) = 2,0154 at the significance level of 5% and the number of degree freedom (df) 44. It meant that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It could be conclude that Mind Reading Game was effective in teaching grammar at the second grade students of MA Darul Kamilin